ChemInform Abstract: Iodine‐Catalyzed Regioselective Thiolation of Flavonoids Using Sulfonyl Hydrazides as Sulfenylation Reagents. Issue 49 (17th November 2016) - Zhao, Xia; Deng, Zhijie; Wei, Aoqi; Li, Boyang; Lu, Kui
Abstract: Regioselective aryl and alkyl thiolation reactions of flavonoid derivatives are described which proceed in position C‐8 for C‐5 hydroxylated flavone, flavonol, dihydroflavone, and isoflavones derivatives, or in position 7 in case of C‐4 hydroxylated aurone derivatives.